Modeling DSC Melting Curves of Isotactic Polypropylene – Source of Information on Isospecificity of Active Centers - Kissin, Yury V. (Journal of Research Updates in Polymer Science, 2013)
A method is developed for modeling DSC melting curves of isotactic polypropylene produced with single-center and multi-center Ziegler-Natta catalysts. The modeling demonstrates that the use of a simple statistical model of an imperfectly isotactic polymer and the introduction of several assumptions about the crystallization pattern of isotactic blocks in propylene polymers are sufficient for the representation of most characteristic features of their DSC melting curves. This type of modeling can be a source of information on the distribution of active centers with respect to isospecificity. Several examples demonstrate the utility of this modeling approach.